Pysicochemical properties and application of edible coatings in strawberry Fragaria x Ananassa) preservation (2018)
The strawberry is one of the most economically important fruit in the Ecuadorian Highlands. Diseases are the main cause of post-harvest losses, causing damage to color, firmness and fruit quality. The main objective of this work was to evaluate the effect of three edible coatings based on gelatin, pectin and beeswax in the post-harvest conservation of the strawberry variety “Oso Grande” from the Chambo canton, Chimborazo province, Ecuador. The process was developed by using a completely random design with factorial arrangement: at room temperature and cooling First, the fruit was selected considering the degree of maturation, size, shape, health of the fruit, and uniform color. Next, it was separated into four groups, washed, and sanitized. Finally, the edible coatings based on gelatin, pectin and beeswax, all enriched with clove essential oil, were applied. The presented physical-chemical changes were evaluated in the two study temperatures. With the obtained results, it could be verified that the use of edible coatings affected statistically in the physical-chemical characteristics of the strawberry. The gelatin coating is the one with the best results, with a lower weight loss of 5.26%, firmness 9.92 N, soluble solids 7.49%, pH 3.69, acidity 0.73% and a shelf life of 5 days. The cost of production for obtaining the gelatin coating was the most economical with a price of $11.10/kg USD. The results show the efficiency of the edible coatings and the storage temperature in the extension of the shelf life of the strawberry.